2016
DOI: 10.1097/mcg.0000000000000544
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Disease in Chinese Chronic Hepatitis B Patients With Low Viral Loads and Persistently Normal Alanine Aminotransferase Levels

Abstract: Among patients presenting with low HBV DNA levels and normal ALT levels, about 38.2% had significant liver disease. Neither serum HBsAg nor HBV DNA levels correlate with liver histology. However, APRI≥0.24 might be considered an indicator of liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…We did not consider immune tolerance as one of the states here, which was common among infants and children, due to less epidemiologic data being available and the largest population comprising chronic HBV infection in adults who were inactive carriers in China [5,[26][27][28].…”
Section: Model Schematicsmentioning
confidence: 99%
“…We did not consider immune tolerance as one of the states here, which was common among infants and children, due to less epidemiologic data being available and the largest population comprising chronic HBV infection in adults who were inactive carriers in China [5,[26][27][28].…”
Section: Model Schematicsmentioning
confidence: 99%
“…Moreover, over half of CHB subjects with normal or mildly elevated ALT values belonged to the patients who possessed advanced liver disease, and most of them showed significant changes in liver pathology, which were in accordance with the outcome of other reports. [33][34][35] On the other hand, the results also suggested that the previous notion that CHB-infected patients with normal biochemical targets had "healthy" livers may be incorrect. Otherwise, the patients might suffer from cirrhosis or even developed liver disease if they only got the diagnosis and guidance according to their clinical data.…”
Section: Discussionmentioning
confidence: 76%
“…In hepatitis B patients, CHB might probably develop in those with normal ALT. [25] Clinically, it was found that in patients with NAFLD, the ALT level was influenced by age, gender, metabolic factor, and so on. [26] Therefore, the ALT level could not be used to confirm the reason of inflammation, and also could not reflect the conditions of real inflammation in the hepatic cells.…”
Section: Discussionmentioning
confidence: 99%